APPROACHES OF POLITENESS SPEECH: APPROACHES OF POLITENESS SPEECH - Qaypova, Bibiruza (Журнал иностранных языков и лингвистики, 2025)
Communication is an undeniable part of people’s life. During this process humans tend to communicate whether verbal or non-verbal forms. For interacting and communicating language is considered as main tool. Humans utilize language to convey speech acts that reflect diverse intentions. A speech strategy is defined as a complex of speech actions aimed at achieving a communicative goal [4;54]. A communicative strategy can be understood as the alignment of communicative actions with the purpose of communication. At the verbal level, a communicative strategy refers to the coordination of speech acts with communicative objectives and conventional linguistic means through which these objectives are realized. In this regard, linguistic politeness may be seen as a system of communicative strategies, supported by conventional linguistic resources.